Exploration of Public Service Quality Dimensions: Case Study of e-KTP Implementation in Sangkapura District, Bawean Island, Gresik Regency - Wati, Izza Milla; Tamrin, M. Husni; Arieffiani, Deasy (Universitas Muhammadiyah Sidoarjo, 2024)
This research aims to explore and understand the quality of public services in making e-KTPs in Sangkapura District, Gresik Regency. The method used in this research is descriptive qualitative, referring to the four factors of Tjiptono's theory (2000). These include Tangible, Reliability, Responsiveness, Assurance and Empathy. In collecting data, this research used observation, interviews and documentation of the research location in Sangkapura District. The research results show that the Sangkapura District Government is always trying to improve the quality of e-KTP services. However, these efforts are still not optimal because there are still deficiencies in the Responsiveness aspect, empathy aspect and there are several obstacles. Such as slow database response and lack of a public complaint suggestion box. Using e-KTP technology is expected to increase efficiency, reduce opportunities for document forgery and so on.